High-intensity interval training modifies energy supply in male artistic gymnastics and improves floor-specific but not pommel horse-specific endurance performance - Seemann-Sinn, A.; Rüdrich, P.; Sandau, I.; Naundorf, F.; Wolfarth, B. (Frontiers in Sports and Active Living, 2025)
Introduction: Well-developed specific endurance performance in artistic gymnastics is a crucial foundation of successful performance. Therefore, the identification of effective training programs for gymnastics-specific endurance performance is an important factor. This study aims to analyze the effectiveness of high-intensity interval training (HIIT) on gymnastics-specific endurance performance and changes in energy supply during floor and pommel horse routines.